The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1051/0004-6361/201220387
|View full text |Cite
|
Sign up to set email alerts
|

A simple prescription for simulating and characterizing gravitational arcs

Abstract: Simple models of gravitational arcs are crucial for simulating large samples of these objects with full control of the input parameters. These models also provide approximate and automated estimates of the shape and structure of the arcs, which are necessary for detecting and characterizing these objects on massive wide-area imaging surveys. We here present and explore the ArcEllipse, a simple prescription for creating objects with a shape similar to gravitational arcs. We also present PaintArcs, which is a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
0
17
0
1
Order By: Relevance
“…Until recently, finding these rare lensed systems required deliberate searches through known galaxy over-densities where the probability of GL is higher (Smail et al 1997;Postman et al 2012;Furlanetto et al 2013). However, follow-up observations of the brightest sources in under-dense regions revealed evidence of GL (e.g., Chapman et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, finding these rare lensed systems required deliberate searches through known galaxy over-densities where the probability of GL is higher (Smail et al 1997;Postman et al 2012;Furlanetto et al 2013). However, follow-up observations of the brightest sources in under-dense regions revealed evidence of GL (e.g., Chapman et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…They found that, when applied to arcs originated from simple elliptical sources, the two methods lead to very similar results. Furlanetto et al (2013) recently presented some tools to model and fit gravitational arcs. Their ArcEllipse method models arc-like images analytically expressing arc shapes as the distortion of ellipses such as one of their main axes is bent into an arc of a circle.…”
Section: Improving the Interface Between Theory And Observationsmentioning
confidence: 99%
“…The arc is thus characterized by four parameters. To allow for asymmetries in the arc shape, Furlanetto et al (2013) suggest to split the length into the sum of a "right-hand" and of a "left-hand" lengths:…”
Section: Improving the Interface Between Theory And Observationsmentioning
confidence: 99%
See 2 more Smart Citations